2011
DOI: 10.1021/cm2003929
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Local Magnetic Environments and Deuteron Mobility in Jarosite (AFe3(SO4)2(OD,OD2)6, A = K, Na, D3O) and Hydronium Alunite ((D3O)Al3(SO4)2(OD)6), from Variable-Temperature 2H MAS NMR Spectroscopy

Abstract: Detailed insight into the magnetic properties and mobility of the different deuteron species in jarosites (AFe 3 (SO 4 ) 2 (OD) 6 , A = K, Na, D 3 O) is obtained from variable-temperature 2 H MAS NMR spectroscopy performed from 40 to 300 K. Fast MAS results in high-resolution spectra above the N eel transition temperature (i.e., in the paramagnetic regime). The 2 H NMR hyperfine shift (δ), measured as a function of temperature, is a very sensitive probe of the local magnetic environment. Two different magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The IR spectrum they published also clearly shows the presence of bending vibrations of the molecular H 2 O and H 3 O + . In further studies of jarosite and alunite-group compounds (Majzlan et al, 2010;Nielsen et al, 2007Nielsen et al, , 2008Nielsen et al, , 2011, a number of well characterized synthetic compounds were examined by various techniques of solid-state NMR. Nielsen et al (2011) concluded that H + ions in H 3 O + groups (or D 3 O + ) at the A site do not react with the OH groups within the framework, distinguishing the distinct resonances attributable to FeO(D)ÀFe, FeÀOD 2 and D 3 O/D 2 O local environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IR spectrum they published also clearly shows the presence of bending vibrations of the molecular H 2 O and H 3 O + . In further studies of jarosite and alunite-group compounds (Majzlan et al, 2010;Nielsen et al, 2007Nielsen et al, , 2008Nielsen et al, , 2011, a number of well characterized synthetic compounds were examined by various techniques of solid-state NMR. Nielsen et al (2011) concluded that H + ions in H 3 O + groups (or D 3 O + ) at the A site do not react with the OH groups within the framework, distinguishing the distinct resonances attributable to FeO(D)ÀFe, FeÀOD 2 and D 3 O/D 2 O local environments.…”
Section: Discussionmentioning
confidence: 99%
“…In further studies of jarosite and alunite-group compounds (Majzlan et al, 2010;Nielsen et al, 2007Nielsen et al, , 2008Nielsen et al, , 2011, a number of well characterized synthetic compounds were examined by various techniques of solid-state NMR. Nielsen et al (2011) concluded that H + ions in H 3 O + groups (or D 3 O + ) at the A site do not react with the OH groups within the framework, distinguishing the distinct resonances attributable to FeO(D)ÀFe, FeÀOD 2 and D 3 O/D 2 O local environments. Based on those spectra, they excluded the previously postulated reaction mechanism based on the interaction of the H 3 O + and OH À resulting in H 2 O formation (Grohol and Nocera, 2007;Grohol et al, 2003) and proposed another mechanism, which involves the formation of M 3+ (Fe or Al) vacancies at the B site and the formation of terminal OH 2 (OD 2 ) groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen from H 3 O and H 2 O at the A site could not be identified; a result that was expected because motion and disorder makes it difficult to locate hydrogen within the cavity surrounding the A site (e.g. Spratt et al 2014;Nielsen et al 2008Nielsen et al , 2011. The estimated residual electron density maxima for hydrogen should be very low The occupancies of the A and B site were studied in two different ways.…”
Section: Crystal Structure Refinementmentioning
confidence: 99%
“…30 However, jarosites are notorious for vacancies on the M site, which locally lift the magnetic frustration and result in local antiferromagnetic correlations. 28 Solid state NMR studies have shown that M-and A-site vacancies are correlated for jarosites with M = Al, Ga, Fe, V, and Cr [29][30][31] resulting in the following defect mechanism,…”
Section: Introductionmentioning
confidence: 99%